Implementasi Pembentukan Karakter Siswa Melalui Program Penerapan 5 S ( Senyum, Sapa, Salam, Sopan, Santun) di SD Muhammadiyah Ambarbinangun Bantul - Maksum, Khanif (Literasi: Jurnal Ilmu Pendidikan, 2018)
This study aims at determining the implementation of 5S programs at Muhammadiyah Elementary School Ambarbinangun Tirtonirmolo Bantul which include: General character education in general, teacher's understanding toward character education through 5S and principals and teachers efforts in building students character through 5S.               This research is a case study qualitative research. Data collection techniques used in this research were interviews and documentation. Data analysis techniques using data reduction, data presentation and conclusion. Data validity techniques used in this research was source and data triangulations.               The results of this study indicate that Muhammadiyah Elementary School, Ambarbinangun has carried out the formation of student character through habituation of the implementation of the 5S as follows: (1) the teacher has understood the nature of character education well, (2) the implementation of the 5S is based on self-development which includes routine school activities, spontaneous activities, exemplary and conditioning. 5S is also implemented in the learning activities through; school’s curriculum, scoring and subjects. The school principal’s roles are coordinating, mobilizing, and harmonizing the implementation of teaching and learning processes at the school. Meanwhile, teachers give the students motivation to have better characters. It can be seen from the students’ routine activities to stay in lines in front of the class before entering each room then shaking hands with the teacher.Keywords: Character building, application of 5 S (senyum, sapa, salam , sopan santun)